Studi Kasus: Dinamika Psikologis dan Peran Terapi Kognitif Perilaku dalam Menurunkan Kecemasan Individu dengan Gangguan Cemas Menyeluruh disertai Serangan Panik - Roselli Kezia Ausie (Humanitas (Jurnal Psikologi), 2025)
This study aims to provide an overview of the psychological mechanisms of individual with Generalized Anxiety Disorder (GAD) accompanied by panic attacks. Cognitive Behavioral Therapy (CBT) was provided in an effort to reduce anxiety symptoms. The intervention was conducted over eight sessions, consisting of psychoeducation, relaxation, cognitive restructuring, and problem-solving exercises. The research method used was a qualitative approach with a case study design involving one participant. Measurements were conducted through interviews, observations, and the Beck Anxiety Inventory questionnaire. The results of the study indicate how cognitive distortions play a role in anxiety disorders. Cognitive Behavioral Therapy found to be an effective approach in reducing anxiety symptoms from severe to moderate. Cognitive distortions, such as the belief in always needing to control everything, changed to a more adaptive way of thinking, where the participant learned to distinguish between things that can and cannot be controlled. Changes in daily activities and problem-solving actions were also observed in the subject. A follow-up three weeks after the intervention showed that cognitive, emotional, and behavioral changes were sustained. Panic attacks were not reported by subject post-intervention.